“No one talks about it”: using emotional methodologies to overcome climate silence and inertia in Higher Education - Pigott, Anna; Nuuttila, Hanna; Thomas, Merryn; Smith, Fern; Bohata, Kirsti; Murray, Tavi; Palser, Marega; Holmes, Emily; Elias, Osian (Frontiers in Sociology, 2024)
Higher Education (HE) is, at best, struggling to rise to the challenges of the climate and ecological crises (CEC) and, at worst, actively contributing to them by perpetuating particular ways of knowing, relating, and acting. Calls for HE to radically transform its activities in response to the polycrises abound, yet questions about how this will be achieved are often overlooked. This article proposes that a lack of capacity to express and share emotions about the CEC in universities is at the heart of their relative climate silence and inertia. We build a theoretical and experimental justification for the importance of climate emotions in HE, drawing on our collective experience of the Climate Lab project (2021–2023), a series of in-person and online workshops that brought together scientists, engineers, and artists. We analyse the roles of grief, vulnerability, and creativity in the conversations that occurred, and explore these exchanges as potential pathways out of socially organised climate denial in neoliberal institutions. By drawing on the emerging field of “emotional methodologies,” we make a case for the importance of emotionally reflexive practices for overcoming an institutionalised disconnect between feeling and knowing, especially in Western-disciplinary contexts. We suggest that if staff and students are afforded opportunities to connect with their emotions about the CEC, then institutional transformation is (a) more likely to happen and be meaningfully sustained and (b) less likely to fall into the same problematic patterns of knowledge and action that perpetuate these crises. This profound, sometimes uncomfortable, emotionally reflexive work is situated in the wider context of glimpsing decolonial futures for universities, which is an integral step towards climate and ecological justice.